Herbivore‐Mediated Competition between Defended and Undefended Plant Species: A Model to Investigate Consequences of Climate Change - Dormann, C. F. (Plant Biology, 2002)
Abstract: Optimal levels of anti‐herbivore defence are determined not only by grazing pressure on the target plant, but also by the efficiency of the defence and by competitive interactions with neighbours. In the high Arctic on Svalbard, grazing by reindeer is a process that can be modelled without plant‐to‐herbivore feedback, as reindeer population sizes are not correlated with plant growth. However, growing conditions are extreme: a short season and low temperatures inhibit optimal growth. Therefore, it is possible to model anti‐herbivore defence in competition in this system, assess how its optimum depends on grazing intensity and defence efficiency, and, finally, how global climate change will effect plant‐plant interactions. This model, based on a Lotka‐Volterra type competition and temperature‐dependent growth, indicates that competition is of considerable importance even in extreme environments. Herbivory mediates displacement of the defended plant by releasing it from competition. This process is more pronounced under high grazing pressure than under low pressure. In other words, competition potentially magnifies the effect of herbivory. Elevated temperatures and a longer growing season have no qualitative impact on these processes, as the dominant defended plant profits most.